2007
DOI: 10.1021/jp071782m
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic−Aromatic Interaction between 2,3,5-Triphenyl-2H-tetrazolium Chloride and Poly(sodium 4-styrenesulfonate)

Abstract: Aromatic-aromatic interactions are found between the cationic molecule 2,3,5-triphenyl-2H-tetrazolium chloride (TTC) and the molecule poly(sodium 4-styrenesulfonate) (PSS) which makes the overall interaction of TTC with PSS more intense than the interaction with other polyanions containing sulfonate groups and produces a decrease on the redox ability of TTC. Diafiltration was used to compare the binding of TTC to PSS, poly(sodium vinylsulfonate) (PVS), and the more hydrophobic poly(sodium 2-(N-acrylamido)-2-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 39 publications
2
47
0
Order By: Relevance
“…We have already reported the high ability of this polymer to bind aromatic cations or zwitterions, due to a suitable complementation of short-range electrostatic forces, nonspecific hydrophobic interactions, and ar/ar interactions. [28][29][30][31][32][33] UV-Vis analyses show that in the presence of small amounts of PSS, the aggregation of MB is also induced in the environment of the polymer, as can be seen in Figure 7 by the disappearance of the monomer band. But as the concentration of PSS increases from an equimolar ratio (in sulfonate groups), the band corresponding to the higher aggregates shifts continuously to 616 nm, revealing the continuous formation of smaller aggregates.…”
Section: Mb In the Presence Of Pssmentioning
confidence: 92%
See 1 more Smart Citation
“…We have already reported the high ability of this polymer to bind aromatic cations or zwitterions, due to a suitable complementation of short-range electrostatic forces, nonspecific hydrophobic interactions, and ar/ar interactions. [28][29][30][31][32][33] UV-Vis analyses show that in the presence of small amounts of PSS, the aggregation of MB is also induced in the environment of the polymer, as can be seen in Figure 7 by the disappearance of the monomer band. But as the concentration of PSS increases from an equimolar ratio (in sulfonate groups), the band corresponding to the higher aggregates shifts continuously to 616 nm, revealing the continuous formation of smaller aggregates.…”
Section: Mb In the Presence Of Pssmentioning
confidence: 92%
“…Thus, the luminescent, [28][29][30] redox, [31] acid/base, [29,30,32] and binding properties [29][30][31]33] of various substrates are modified by this method. Ar/ar interactions are one of the principal noncovalent forces governing molecular recognition and biomolecular structure.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the extracted ternary complex has a composition of 1 : 1 : 2 (Fe-4NC-TTC). One can conclude that the Fe(II)-4NC anionic chelate has a double negative charge, since TTC forms monovalent cation (TT + ) [13,[15][16][17][18][19][20][21][22][23][24][25][26] and the Fe(II)-to-TTC molar ratio is 1 : 2 ( Fig. 5, 2).…”
Section: Doi: 101134/s1070363215080241mentioning
confidence: 99%
“…We previously reported [13] a liquid-liquid extraction-chromogenic system containing Fe(III), 4NC, and a widely used [15][16][17][18][19][20][21][22][23][24][25][26] cationic ion-association reagent, 2,3,5-triphenyl-2H-tetrazolium chloride (TTC). The next step, study of a similar system containing Fe(II) instead of Fe(III), is accomplished here.…”
mentioning
confidence: 99%
“…Among aromatic counterions, the tetrazolium salt 2,3,5‐triphenyl‐2 H ‐tetrazolium chloride (TTC) has been used . It was seen by diafiltration and 1 H‐NMR, that aromatic–aromatic interactions between the tetrazolium salt and polymers bearing BS groups occur, and the strength of the interaction directly correlates with the linear aromatic density.…”
Section: Introductionmentioning
confidence: 99%